METHODS OF TEACHING ENGLISH ON THE BASIS OF INTERNATIONAL STANDARDS - Turakulova Umida Akmaljon qizi (Web of Journals Publishing, 2024)
This article describes methods of teaching English based on international standards, competency-based approach and "Flipped Classroom" method.
Keywords: competency-based approach, communication-based, interactive programs, online platforms, virtual classrooms, goal-oriented learning, active reading and writing.